2004
DOI: 10.1530/eje.0.1500663
|View full text |Cite
|
Sign up to set email alerts
|

Circulating adiponectin levels and cardiovascular risk factors in acromegalic patients

Abstract: Objective: Adiponectin (ApN) is an adipocytokine expressed in human adipose cells with anti-atherogenic and anti-inflammatory properties that plays a role in the pathophysiology of insulin resistance, metabolic syndrome and coronary artery disease. The aim of the study was to evaluate ApN secretion in patients with acromegaly, a chronic disease associated with insulin resistance and increased cardiovascular mortality, and to correlate ApN levels with hormonal, metabolic and cardiovascular parameters. Design an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 38 publications
3
14
0
Order By: Relevance
“…Silha et al [39] showed increased adiponectin levels in acromegalic patients, without direct or inverse correlation with metabolic or hormonal parameters, probably because adiponectin are negatively correlated with body fat, which is reduced in acromegaly [46]. In the current study, we found no significant difference in adiponectin levels between uncontrolled and controlled patients, as well as in the different treatment groups, and these results are consistent with those of Ronchi et al who did not demonstrate the validity of adiponectin as a marker of cardiovascular risk, because the lack of correlation with BMI, hormonal and metabolic parameters [47]. Therefore, acromegaly would differ from the other conditions of insulin resistance that are associated with hypoadiponectinemia [48,49].…”
Section: Discussionsupporting
confidence: 91%
“…Silha et al [39] showed increased adiponectin levels in acromegalic patients, without direct or inverse correlation with metabolic or hormonal parameters, probably because adiponectin are negatively correlated with body fat, which is reduced in acromegaly [46]. In the current study, we found no significant difference in adiponectin levels between uncontrolled and controlled patients, as well as in the different treatment groups, and these results are consistent with those of Ronchi et al who did not demonstrate the validity of adiponectin as a marker of cardiovascular risk, because the lack of correlation with BMI, hormonal and metabolic parameters [47]. Therefore, acromegaly would differ from the other conditions of insulin resistance that are associated with hypoadiponectinemia [48,49].…”
Section: Discussionsupporting
confidence: 91%
“…Adiponectin has anti-atherogenic and anti-inflammatory properties with direct effects on endothelial cells and macrophage-to-foam cell transformation. We and others (38,39) failed to find any difference in levels of adiponectin between active acromegaly and controlled disease. These results support the view that adiponectin levels do not significantly improve during treatment of acromegaly.…”
Section: Discussionmentioning
confidence: 59%
“…Data regarding adiponectin levels in active acromegaly available in the literature is variable as lower than [22], higher than [18] or similar to [19,20] those in normal controls. The effect of GH-reducing therapy on serum adiponectin levels has also been studied [21,22].…”
Section: Discussionmentioning
confidence: 96%